Analysis of Demographic and Staging Characteristics in Patients with Colorectal Cancer Using the SEER Registry - Devanaboyina, Monika (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.